Caminhos e descaminhos na implantação da política de assistência social no Município de Junco do Seridó-PB - Oliveira, Luciana Batista de (2010)
From the 1988 Constitution, Social Assistance Policy becomes a guaranteed right. The approval of the Organic Law of Social Assistance and the creation of the Unified Social Assistance Service (SUAS) are examples that make up the foundations of this model of social management, decentralized and participatory. The SUAS operates in a decentralized manner and with financial transfers from National Fund to Municipal Social Assistance Fund. It also occurred to empowering municipalities in Managements initial, basic or full. This study aims to present how was the whole process of implementation of this system in the municipality of Junco do Seridó-PB, describing the process of enabling the municipality, the actions of CRAS, Federal Programs running in the city and the view of technical acted directly on its implementation, determining the limits and possibilities that this model presented in that district. The city was certified in Basic Management, for providing basic social protection services and of medium complexity, such as the PETI and PBF. The council presents the minimum conditions for the implementation of programs, but with limitations that are peculiar to small towns, especially in reality of Paraíba, with limited resources and scarce jobs. Shares of CRAS meet all generational groups, from young children in the Toy Library as the elderly, to the accompaniment of a multidisciplinary team composed of assistance, health and education professional. Identified as possibilities, as described in statements of the authors when they point out the social achievements, and express the positive results of actions taken at the council, such as the development of Federal Programs and actions of CRAS. However, limits are identified as the lack of ongoing training, lack of access to media such as internet and telephone. We propose an involvement of professionals, managers and all who are part of this construction of social policy, to seek knowledge beyond what is put in by government agencies, so that together, with the institutions of knowledge, we can change our practice in a praxis, for the guarantee of citizenship for all.